The application of the two stay two stray (TSTS) model to improve student learning outcomes in social studies learning in schools - Nawawi, Iqbal; Ridwan, Ita Rustiati (International Conference on Education in Primary and Early Childhood, Marine, Computer Information, and Logistics, 2025)
An effective learning model is the key to achieving quality learning outcomes. However, conventional learning methods such as lectures are often less able to actively engage students, so students' participation and academic achievement are less optimal. This research is motivated by the low learning outcomes of grade IV students of SDN 1 Parungsari in the subject of Natural and Social Sciences (IPAS). This study aims to improve student learning outcomes and their active involvement through the application of the Two Stay Two Stray (TSTS) type of Cooperative Learning model. This study uses the Classroom Action Research (PTK) method which is carried out in three cycles, with a qualitative approach and data collection techniques in the form of observations, interviews, and tests. The results show that the TSTS model is effective in increasing student active engagement and creating a more interactive and collaborative learning environment. This model encourages students to actively participate in group discussions and strengthen their understanding of the material through the exchange of information between groups. Further research is suggested to adapt this model to other subjects to expand the positive impact on improving student learning outcomes.
Keywords: cooperative learning; two stay two stray; learning outcomes; natural and social science learning